Computing Fundamentals and C Programming - E. Balagurusamy (McGraw Hill Education ( india) Private Limited, 2008)
The first variant of the two, this book discusses fundamentals of computers along with C programming aspects in great detail. The course fit is Introduction to Computing/Fundamentals of Computers. A syllabus analysis would reveal that there are two types of course structures, one where programming is mixed with fundamentals and the other is where only fundamentals are covered. This text is designed to the cover former.